Development of Professional Activities of Nurses in an Independent Latvia (1991-1999) - Odiņa, Olga; Sargsjane, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays Latvian nurses work in health care institutions, or are self-employed, providing independently patient care, participating in treatment, managing patient care work, educating patients, their family members, care team members and society. Modern nursing qualification is equal to the international level. To reach this level it was necessary to reform nursing professional development (education, registration, re-registration and introduction of nursing certification), which took place during the first ten years of Latvian restoration of independence.